EGO TOKOH UTAMA DALAM CERPEN KELUARGA M KARYA BUDI DARMA (KAJIAN PSIKOANALISIS) - Raisha Fujianty Sofyan; Dini Samsiah; Siti Maemunah (Jurusan Pendidikan Bahasa dan Seni Fakultas Keguruan dan Ilmu Pendidikan Universitas Lampung, 2026)
For This study aims to analyze the role of the “I” character’s ego as the agent of aggressive impulses and to identify the forms of ego defense mechanisms used to maintain psychological stability in Budi Darma’s short story Keluarga M. The research method employed is qualitative descriptive, using a literary psychology approach grounded in Sigmund Freud’s psychoanalytic theory. The results of the study reveal massive ego dysfunction in the first half of the story, where the ego of the “I” character aligns with the id’s aggressive impulses to orchestrate destructive sabotage as a result of external frustration. However, the momentum of a tragic accident serves as a psychological turning point for the character. The ego mitigates this anxiety through defense mechanisms, including rationalization, repression, isolation of effects, dissociation, reaction formation, and social sublimation in the form of disability advocacy. In conclusion, the “I” character’s ego ultimately succeeds in achieving a complete psychological reconstruction, thereby reaching a new, rational state of equilibrium (homeostasis) in accepting his existential solitude by the story’s end. At the same time, this reveals the dark defensive tactics of the ego in Budi Darma’s fiction. Penelitian ini bertujuan untuk menganalisis peran ego tokoh “Saya” sebagai pelaksana dominasi dorongan agresi serta mengidentifikasi bentuk mekanisme pertahanan ego yang digunakan untuk menjaga kestabilan psikis dalam cerpen Keluarga M karya Budi Darma. Metode penelitian menggunakan adalah deskriptif kualitatif dengan pendekatan psikologi sastra berlandaskan teori psikoanalisis Sigmund Freud. Hasil penelitian menunjukan disfungsi ego yang masif pada paruh awal cerita, dimana ego tokoh “Saya” bersekutu dengan dorongan agresi id untuk merancang sabotase destruktif akibat frustasi eksternal. Namun, momentum kecelakaan tragis menjadi titik balik kejiwaan tokoh. Kecemasan tersebut diredam ego melalui mekanisme pertahanan diri (self-defense mechanism), meliputi rasionalisasi, represi, isolasi efek, disosiasi, reaction formation, hingga sublimasi sosial berupa advokasi disabilitas. Kesimpulannya, ego tokoh “Saya” pada akhirnya berhasil melakukan rekonstruksi kejiwaan secara utuh sehingga mencapai titik keseimbangan baru (homeostasis) yang rasional dalam menerima kesendirian eksistensialnya di akhir cerita. Sekaligus membongkar taktik pertahanan ego yang kelam dalam fiksi Budi Darma.